Cell and molecular biology - Karp, Gerald
Balances coverage of the concepts of cell and molecular biology, using examples of experimentation to support those concepts. As experimental techniques become more diverse and complex, it is increasingly necessary to identify individual studies that have a broad impact on our understanding of cell biology. This text describes in detail some of the key experimental findings, along with the original data and figures